Expanding first-line options for depression: Protocol of a pragmatic comparative effectiveness trial of yoga vs. behavioral activation (the COMPARE study) - Louisa G. Sylvia; Andrew M. Busch; Dustin J. Rabideau; Alexandra Gold; Suzanne C. Danhauer; Heather T. Schatten; Douglas Katz; Lauren M. Weinstock; Jennifer Dahne; Sabine P. Schmid; Zainab Soetan; Roberta Tovey; et al. (PLoS ONE, 2025)
Depression is a prevalent mental health condition in the United States and a significant cause of morbidity and mortality. The treatment guidelines for depression recommends either psychotherapy, such as behavioral activation (BA), or a second-generation antidepressant as a first-line treatment for adult patients with depression. However, many individuals with depression do not experience improvement from first-line treatments or choose not to engage in them due to stigma, cost, difficulty with access, and/or side effects. As such we need new treatments for depression and yoga is especially promising given recent data on its efficacy for depression. This study seeks to compare a first-line treatment for depression, or BA, versus yoga to examine whether yoga does as well as BA at improving depressive symptoms and secondary outcomes. We will also examine improvements in depressive symptoms, and secondary outcomes, by specific sub-populations to determine who might do better in which treatment (i.e., BA or yoga). Given that this is the first non-inferior, comparative effectiveness study of yoga, this paper explains the study design, the rationale for the study design, as well as lessons learned in conducting the study.